The biomechanics of vertical hopping: A review - Lamontagne, M.; Kennedy, M. J. (Research in Sports Medicine, 2013)
Repetitive vertical hopping is a simple and relatively controlled task useful for studying basic neuromuscular properties and tissue mechanics. However, several biomechanical and physiological factors are involved. This article provides an overview of muscle and tendon properties and how these interact during vertical hopping. Muscle properties discussed are force-velocity and force-length relationships, electromechanical delay, muscle fiber type, stretch induced contraction amplification, and muscle spindle afferent feedback. Tendon properties include storage and reuse of elastic energy, tendon stiffness, afferent information from Golgi tendon organs, and failure points. These muscle and tendon properties interact to generate vertical hopping force and power. In addition to these basic properties, there are other more complicated factors to consider when analyzing vertical hopping such as balance and coordination. A wealth of information can be gathered by studying vertical hopping. Caution should be taken, however, to prevent inappropriate conclusions being drawn about hop performance due to oversimplification.